PRIMITIVE FUTURE: METAL, TIME, AND NEOLIBERALISM IN SEPULTURA MUSICAL PRODUCTION (1989) - Alecrim, Thales Reis [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2023)
Primitive Future, the final track from the Brazilian band Sepultura's album Beneath the Remains (1989), marked the global emergence of the ensemble and subsequent commercial success. Musically, the song is centered on a pulsating rhythm and horizontal motifs (riffs) developed at a rapid pace. Additionally, it lacks a defined tonal center, creating a tense atmosphere through consonances and dissonances. The lyrics also depict a post-apocalyptic future. Thus, this study explores the historical conditions that allowed the production and circulation of a pessimistic song about the future. It specifically examines the rise of neoliberalism and presentism alongside the establishment of capitalist realism and performance as a social imperative in a globalized context.
Keywords: metal; neoliberalism; presentism